Projeto e imagem como política urbana sobre a produção contemporânea da arquitetura institucional pública em Fortaleza-CE - Arruda, Daniel Marques (2018)
All public institucional architecture emerges from a specific political, social and economic condition. It takes the public sector's signature, but it is the result of impasses among different urban actors: the private segment, groups of interest or groups of pressure. Technique and aesthetics will follow up in an attempt to materialize these intentions or subvert them. Therefore, it is vital to ask what the role of this architecture, which is requested and conceived in favor of and as representation of public politics, is and what it contributes to the production of the urban space. Would it constitute a declaration of a domineering strategy forged upon deeply rooted behavior of social domineering grupos? Would it mean just a pragmatic link of economic political conjunctural interests? Considering the architetonic image a central component for the conception and interpretation of new socialspace dynamics adjusted to model, the starting point of this present paper is the assumption that, nowadays, the main mission of public institutional architecture is to give support to the globalized neoliberal imperatives. Based on this premisse, the main objetive of this research is to look into how the political-ideological architecture alignment of the public institutional architecture in the State of Ceará becomes effective, as of 1990, and its repercussions in the capital city of Fortaleza. In such perspective, two projects which offer an image-synthesis of the regional hegemonic group in power, since the 90's: Centro Dragão do Mar de Arte e Cultura (CDMAC, 1999) and Centro de Eventos do Ceará ( CEC, 2009). Bearing in mind the objective to prove the continuity of this strategy, a third project - Acquário do Ceará - still undergoing construction, was also analysed. This was proved and decoded through research methodology which articulates three analytical dimensions: (a) the analysis of the political and institutional contexts; (b) the analysis of pragmatic content of project discourse; (c) the evaluation of socialspace repercussions after its occupation and use.